Why many Batesian mimics are inaccurate: evidence from hoverfly colour patterns - Taylor, Christopher H.; Reader, Tom; Gilbert, Francis (Royal Society, 2016)
Mimicry is considered a classic example of the elaborate adaptations that natural selection can produce, yet often similarity between Batesian (harmless) mimics and their unpalatable models is far from perfect. Variation in mimetic accuracy is a puzzle, since natural selection should favour mimics that are hardest to distinguish from their models. Numerous hypotheses exist to explain the persistence of inaccurate mimics, but most have rarely or never been tested against empirical observations from wild populations. One reason for this is the difficulty in measuring pattern similarity, a key aspect of mimicry.